The legend of the persian carpet - De Paola, Tomie; Ewart, Claire (New York : G.P. Putnam's Sons, 1993)
Tells how the first Persian carpet was created to replace King Balash's lost treasure.
Keywords: Folklore -- Iran; Carpets -- Folklore